E-COMMERCE DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Misbakhul Munir Mubarok (Sekolah Tinggi Pariwisata Mataram, 2022)
The development of science and technology, the more developed the method used in the buying and selling process. E-commerce is an innovation in the business world where contract actors are far from each other and it is not possible to be present in one place. This study aims to analyze the practice of e-commerce based on the perspective of Islamic economic law. The research method used is a literature study using a qualitative approach. This study found that e-commerce is the same buying and selling activity using Bai` As-salam buying and selling. E-commerce can be justified if it fulfills the obligations of buying and selling Bai` As-salam.